A study of patients with isolated mediastinal and hilar lymphadenopathy undergoing EBUS-TBNA. Issue 1 (2nd June 2014) - Evison, Matthew; Crosbie, Philip A J; Morris, Julie; Martin, Julie; Barber, Philip V; Booton, Richard
Abstract : Background: Isolated mediastinal and/or hilar lymphadenopathy (IMHL) may be caused by benign and malignant disorders or be 'reactive'. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has a reported low negative predictive value (NPV) in IMHL, necessitating mediastinoscopy in selected patients. The aim of this study was to examine the NPV of EBUS-TBNA in an IMHL population and determine whether clinical variables differentiate between pathological and reactive IMHL. Methods: Analysis of a prospectively maintained database of consecutive patients with IMHL referred to a single UK centre for EBUS-TBNA. Results: 100 patients with IMHL had EBUS-TBNA during the study (March 2010–February 2013), mean age 58.6±15.7 years, 63% men, 70% white British and mean follow-up 16.8±8.6 months. Pathological cause of IMHL established in 52 patients (sarcoidosis n=20, tuberculosis n=18, carcinoma n=7, lymphoma n=6, benign cyst n=1), 43 from EBUS-TBNA. 48/57 negative EBUS-TBNA samples were true negatives reflecting reactive lymphadenopathy in 48%. The diagnostic accuracy of EBUS-TBNA was 91% and NPV was 84.2% (95% CI 72.6% to 91.5%). Multivariate analysis of clinical covariates showed age (odds ratio (OR) 1.07, 95% CI 1.01 to 1.13; p=0.033), the presence of a relevant comorbidity (OR 9.49, 95% CI 2.20 to 41.04; p=0.003) and maximum lymph node size (OR 0.70, 95% CI 0.59 to 0.83; p=0.00004) to differentiate between reactive and pathological IMHL. Stratification of the study population according to comorbidity and maximum lymph node size (<20 mm) identified a low-risk cohort (n=32) where the NPV of EBUS-TBNA was 93.8% (95% CI 79.9% to 98.3%). Conclusions: Reactive lymphadenopathy accounts for a significant proportion of patients with IMHL. In carefully selected patients with IMHL and a negative EBUS-TBNA, surveillance rather than further invasive sampling may be an appropriate strategy.